PENGAWASAN ORANG TUA TERHADAP TONTONAN TELEVISI DAN PENGARUHNYA TERHADAP KEDISIPLINAN ANAK - Dhin, Cut Nya (Universitas Islam Negeri Ar-Raniry, 2020)
Television broadcasts that are not in accordance with Islamic teachings, make children can watch whenever and wherever the broadcasts are. Therefore parents are needed supervision to select every television program watched by children. The problem in this study is parental supervision of television viewing and child discipline, as well as the efforts made by parents in increasing supervision of television viewing and child discipline, the constraints that become the population In this study are children aged 6-14 years, a total of 102 children and a sample of 30 children (30%). The methodology used in this study is field research. Data collection techniques used were observation, interviews, questionnaires and documents. The results showed that parental supervision of children's television viewing was not optimal. Obstacles faced by parents in supervising television viewing and child discipline are busy parents who work outside the home, lack of parental knowledge and parental indifference to television viewing supervision. Parents do not make any effort When children watch television that is violent/pornographic, but only a few who turn off the television and explain that these conditions are not good.